Peningkatan profesionalisme guru melalui pelatihan penulisan karya tulis ilmiah - Purnamawati Purnamawati; Usman Mulbar; Ahmad Zaki (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
PKM program was carried out by providing trainingand mentoring activities to participants regarding ScientificWriting (KTI). The program was done to improve teacherprofessionalism with the aims of (1) to increase knowledgeabout scientific writing, (2) participants can implementscientific papers well in its duties, and (3) participants candisseminate knowledge of scientific papers. The main targetparticipants in this PKM Program activities were schoolsupervisors, school principal, and teachers in theTinggimoncong District, Gowa Regency, South-SulawesiProvince. The results obtained in this PKM program included:1) Knowledge, concepts, and development of scientific papersof PKM program participants increased, 2) PKM programparticipants know the types of scientific writing, 3) PKMprogram participants know the techniques and ways of writingscientific papers, and 4) PKM program participants cancompile and write scientific papers. Other results obtainedwere the increase in participants' motivation in understandingthe material of scientific writing and high enthusiasm ofparticipants in disseminating the results of PKM program,especially the information related to the scientific writing.